Development of online learning videos as digital learning media for health promotion students - Yuni Fatimatizzahro; Erick Zicof; Risanita Fardian Farid (PT WIM Solusi Prima, 2026)
The rapid advancement of digital technology in education has created a growing need for innovative learning media that support student-centered learning while enhancing the quality of the learning process. This study aimed to develop a digital learning medium in the form of online instructional videos to upgrade the public speaking skills of students as prospective health promoters, as well as to evaluate the media's validity, practicality, and user responses. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants consisted of 36 students enrolled in the Applied Bachelor's Degree Program in Health Promotion at Poltekkes Kemenkes Padang. Data were collected through interviews, questionnaires, and documentation, and were analyzed using descriptive quantitative and qualitative approaches. The findings revealed that the online instructional videos achieved validation scores of 4.43 from the subject matter expert and 4.36 from the media expert, both of which were categorized as highly valid. In addition, students' responses yielded an average score of 4.41, indicating a very positive level of acceptance, particularly in terms of ease of use, visual appeal, clarity of content delivery, and their ability to enhance learning motivation. The findings further demonstrated that the developed learning media effectively promoted students' learning motivation, active engagement, and understanding of public speaking concepts relevant to the competencies required of future health promoters in a digital learning environment.